Formulasi dan Uji Efektivitas Umbi Bit Merah (Beta Vulgaris L. var Lubra L) Pada Kosmetika Lip Scrub - Nafisah Isnawati (LPPM STIKes Prima Indonesia, 2020)
Red beetroot (Beta Vulgaris L. var Lubra L) is plant that contains betacyanin which is antioxidant and can be used as a natural coloring. The aims of this study is to formulate and test the effectiveness of lip scrub preparations using natural beetroot ingredients. Research on lip scrub formulations made from sucrose, honey and red beetroot extract with levels of 10%, 15%, and 20%. Evaluations include physical quality test, pH test, melting point test, irritation test temperature influence and storage duration test. Research results from the extraction process obtained the best results without using ethanol and water solvents. From the results of the study it was found that the concentration of color with 10% beetroot levels obtained pink, 15% concentrated pink, and 20% dark red based on organoleptic tests. Lip scrub content of 20% is the mostly request based on the color, the scent, and texture with a significance value is 0.015. While the texture for 20% content is 3,56. From the hedonic test of color, the scent, and texture with a 20% of content which is very preferred, while for 10% and 15% of content are included in the scale preferred by panelists. The pH of the observations was 5 and the melting point was 160 ° C - 170 ° C. Storage temperature at room temperature and temperature of 20 ° C obtained the most effective preparation at 20% and100% irritation test found no irritation.